Getting Published in Top Journals: Is the Deck Stacked Against You? - Carrothers, Andrew G.; Yao, Liufang; Yao, Liuchang (Issues in Economics and Business, 2021)
We examine the challenges of publishing in top academic journals. We introduce a new data set summarizing 30 years of articles at the three top finance journals. We quantify the issue by first examining the number of articles and authors per year at each journal then comment on the impact of repeat authors and institutional affiliation. Our results show that a small number of academics and institutions dominate the available publishing space in these journals. We then shift the focus to the potential impact of choice of research area on publication success by investigating trends in the coverage of behavioral finance in these journals. Our results suggest an editorial bias against this arguably important field of study.